Observations of long-term change in an African rain forest - Sheil, Douglas (Tropenbos International, 2003)
This account summarises studies based on tree data from plots established during the 1930s and 1940s in Budongo, a Ugandan rain forest. The original interpretations of forest change provoked controversies that continue to the present day. Analyses have yielded three categories of results: the first is descriptive; the second is a more focused evaluation of the relationship between forest change and species persistence; and the third is methodological. This summary focuses on the first two by examining stem, species and stand level patterns of change and introduces some previously unpublished results relating to trends in species traits and characters. Evidence confirms the successional nature of the original series of plots. However, the time series changes are complex and while the younger vegetation plots develop more or less as expected the older plots do not. Disturbances caused by silvicultural intervention in four of the five longer-term plots compromise some evaluations, but also allow the effects of such disturbances to be observed. Various anticipated aspects of forest change are verified. Examples include the slowing of forest dynamics with maturity, and the increase in potential canopy height. However, other observations, such as the real-time increase in tree recruitment are less expected and require explanation. Viewed overall, the results suggest an interplay of many factors that must be explored in greater depth. The importance of truly long-term studies is highlighted.